Free Radicals, Antioxidants and Diseases - Ahmad, Rizvan (IntechOpen, 2018)
The current book entitled Free Radicals, Antioxidants, and Diseases gives an idea of detecting free radicals in vivo by newer techniques and provides insights into the roles played by various antioxidants in combating diseases caused by oxidative stress. The chapters included in this volume showcase new investigation in this field by the research groups around the world.